The Most Recent Advances in the Application of Nano-Structures/Nano-Materials for Single-Cell Sampling - Xu, Xiaolong; Jia, Jianbo; Guo, Mingquan (Frontiers in Chemistry, 2020)
The research in endogenous biomolecules from a single cell has grown rapidly in recent years since it is critical for dissecting and scrutinizing the complexity of heterogeneous tissues, especially under pathological conditions, and it is also of key importance to understand the biological processes and cellular responses to various perturbations without the limitation of population averaging. Although conventional techniques, such as micromanipulation or cell sorting methods, are already used along with subsequent molecular examinations, it remains a big challenge to develop new approaches to manipulate and directly extract small quantities of cytosol from single living cells. In this sense, nanostructure or nanomaterial may play a critical role in overcoming these challenges in cellular manipulation and extraction of very small quantities of cells, and provide a powerful alternative to conventional techniques. Since the nanostructures or nanomaterial could build channels between intracellular and extracellular components across cell membrane, through which cytosol could be pumped out and transferred to downstream analyses. In this review, we will first brief the traditional methods for single cell analyses, and then shift our focus to some most promising methods for single-cell sampling with nanostructures, such as glass nanopipette, nanostraw, carbon nanotube probes and other nanomaterial. In this context, particular attentions will be paid to their principles, preparations, operations, superiorities and drawbacks, and meanwhile the great potential of nano-materials for single-cell sampling will also be highlighted and prospected.